2020
DOI: 10.1126/sciadv.aay2587
|View full text |Cite
|
Sign up to set email alerts
|

Virus-host coexistence in phytoplankton through the genomic lens

Abstract: Virus-microbe interactions in the ocean are commonly described by “boom and bust” dynamics, whereby a numerically dominant microorganism is lysed and replaced by a virus-resistant one. Here, we isolated a microalga strain and its infective dsDNA virus whose dynamics are characterized instead by parallel growth of both the microalga and the virus. Experimental evolution of clonal lines revealed that this viral production originates from the lysis of a minority of virus-susceptible cells, which are regenerated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 48 publications
(59 reference statements)
2
41
0
Order By: Relevance
“…The vast majority (95%) of non-VIPs may not have a significant impact on CEE, because they do not strongly impact the host population, for instance, by stably coexisting with their hosts. It is worth noting that experimental studies have reported cultures of algae with viruses that reach a stable co-existence state after a few generations ( Yau et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority (95%) of non-VIPs may not have a significant impact on CEE, because they do not strongly impact the host population, for instance, by stably coexisting with their hosts. It is worth noting that experimental studies have reported cultures of algae with viruses that reach a stable co-existence state after a few generations ( Yau et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we explored the potential of an untargeted metabolomic approach including pigments, lipids, and other uncharacterized metabolites to investigate chemotaxonomic markers in 12 marine microalgal strains from 11 species, including 9 microalgae from the green lineage; the Mamiellales Ostreococcus tauri [20], O. mediterraneus [21], Bathycoccus prasinos [22], Micromonas commoda [23], and Mantoniella sp., the Chlorellales Picochlorum costavermella [24], and strains from basal groups Nephroselmis sp. and Pyramimonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…They can be easily cultured in the laboratory, witnessed by more than 300 strains maintained in the Roscoff Culture Collection (RCC) in France [1], and they diverged at the base of the green lineage that includes land plants, thus providing a starting point for phylogenetic analyses [2]. Several of their streamlined haploid genomes have been completely sequenced and analysed [3,4,5,6,7,8], and they harbour a minimal number of genes for cellular processes, as reflected in the size of their nuclear genomes. Species in the genus Ostreococcus, for example, which so far includes four phylogenetically divergent [9] species with fully sequenced genomes (see [3,4,8] and ), have only 12–14 Mb of nuclear DNA, comparable to that of yeast (12.1 Mb) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several of their streamlined haploid genomes have been completely sequenced and analysed [3,4,5,6,7,8], and they harbour a minimal number of genes for cellular processes, as reflected in the size of their nuclear genomes. Species in the genus Ostreococcus, for example, which so far includes four phylogenetically divergent [9] species with fully sequenced genomes (see [3,4,8] and ), have only 12–14 Mb of nuclear DNA, comparable to that of yeast (12.1 Mb) [10]. This is much smaller than those of other model species in the green lineage such as mosses ( Physcomitrella patens , 476 Mb, [11]) Arabidopsis thaliana (135 Mb [12]) or maize (2.4 Gb [13]).…”
Section: Introductionmentioning
confidence: 99%